The Effect of Boiled Water of Kemis Mas Ngur (Atactodea striata) on The Nutrition and Organoleptics of Noodle Sauce - Jumrawati, Jumrawati; Angreni, Husni; Syahrin, Muh Alfi (Jurnal Biologi Tropis, 2024)
Mas Ngur clams are usually processed by boiling and the boiled water is simply thrown away. The people of Kei, Southeast Maluku, have long used this clam as a traditional medicine for jaundice by eating the meat and drinking the boiled water. This research aims to determine the nutritional content and organoleptic value of boiled water from mas ngur clams (Atactodea striata) which will be used as soup for noodles. This research was carried out from August to September 2019. Samples of mas ngur clams (Atactodea striata) were taken from Kapoposang Island, Pangkep Regency, South Sulawesi. Sampling was carried out using the Completely Randomized Design (CRD) method with a simple random sampling technique. Data analysis using ANOVA. The results of the research showed that the highest average protein value was sample (C) 10.73% with a treatment concentration of 300g and the highest average fat content was sample (C) 0.13% with a treatment concentration of 300g. Meanwhile, the highest organoleptic taste averages were in sample (C) with a concentration of 300g, namely 7.20 and 7.00. Average organoleptic color of the sample (C) with a treatment concentration of 300g. The highest average texture organoleptic value in sample (C) with a 300g concentration treatment was 7.00 and the highest aroma organoleptic value in sample (A) with a 200g concentration treatment was 7.73. The conclusion of the analysis of variance results showed that the boiled water of mas ngur clams (Atactodea striata) had a significant effect on protein content (p>0.05) and had no significant effect on fat content values (p<0.05) and had no significant effect on organoleptic values (p<0.05).